Fostering Innovation at Work: The Synergy of Transformational Leadership, Job Autonomy, and Innovative Organizational Culture for Driving Innovative Work Behavior. - Oh, Seongdeok; Sabharwal, Meghna (Public Personnel Management, 2026)
While previous studies have identified transformational leadership, job autonomy, and innovative organizational culture as key factors influencing employees' innovative work behavior within public organizations, the interactive effects remain underexplored. To address this gap, this study draws on leader–member exchange, self-determination, and job characteristics theories to examine how these elements synergistically contribute to employees' innovative work behavior. Using survey data from 4,133 South Korean public servants in central and local government, this study employs partial least squares structural equation modeling to test the moderated mediation framework. The findings reveal that transformational leadership is positively associated with innovative work behavior, with job autonomy partially mediating this relationship. It also suggests that an innovative organizational culture has not only direct and moderating effects of transformational leadership on job autonomy but also on innovative work behavior. Ultimately, it highlights that when public employees perceive a high level of innovative organizational culture, the indirect effect of transformational leadership on innovative work behavior, mediated by job autonomy, becomes more pronounced. This study concludes by discussing the theoretical and practical implications of these findings, as well as future research, and emphasizes the critical role of public organizations in creating environments that support innovation among public employees.